2012
DOI: 10.1108/01425451211267900
|View full text |Cite
|
Sign up to set email alerts
|

Labour market experiences of skilled British migrants in Vancouver

Abstract: Purpose: The aim of the paper is to explore the labour market experiences of highly skilled migrants from developed countries who are not linguistic or visible minorities in the host country. Design/methodology/approach: The results of the paper derive from interviews with 64 highly skilled British migrants in Vancouver. Participants were asked open-and closed-ended questions and the data from the interviews were coded and analysed manually. Findings: British migrants were divided with their labour market outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…For example, Oikelome and Healy's () study on domestic‐qualified and overseas‐qualified doctors in the UK found that, although overseas‐qualified doctors earned more than their domestic counterparts, they also worked longer hours and had lesser autonomy and lower levels of morale. Similar mixed evidence was also indicated by Harvey (), who studied British migrants in Vancouver and found that while some had positive experiences, including better salaries, others reported negative experiences. It was also found in some contexts that while migrants did not face barriers in low‐wage jobs, they did so in high‐wage positions (Skuterud and Su, ).…”
Section: Theory Model and Hypothesesmentioning
confidence: 99%
“…For example, Oikelome and Healy's () study on domestic‐qualified and overseas‐qualified doctors in the UK found that, although overseas‐qualified doctors earned more than their domestic counterparts, they also worked longer hours and had lesser autonomy and lower levels of morale. Similar mixed evidence was also indicated by Harvey (), who studied British migrants in Vancouver and found that while some had positive experiences, including better salaries, others reported negative experiences. It was also found in some contexts that while migrants did not face barriers in low‐wage jobs, they did so in high‐wage positions (Skuterud and Su, ).…”
Section: Theory Model and Hypothesesmentioning
confidence: 99%
“…A particularly relevant body of literature for our present purpose is the one looking at the role of social capital in migration and settlement. Within migration studies, the notion of social capital has been widely deployed to explain the critical role that kinship and friendship networks play in facilitating migratory processes as new migrants often move to destinations where there is an already existing concentration of compatriots and/or established ethnic communities (eg Reynolds, 2010; Harvey, 2008, 2012; Haug, 2008; Boyd, 1989). Migrant social networks contribute to the decision to migrate by providing information about job opportunities, and support the mobility process through providing resources and facilitating new migrants' integration into the destination society (Portes, 1998; Eve, 2010).…”
Section: Theoretical Resourcesmentioning
confidence: 99%
“…Their cost-benefit perspective tends to overlook the importance of social networks and structural challenges (Harvey, 2012). For instance, suggest that QIs' career success and satisfaction in host economies is strongly influenced by their ethnic origin.…”
Section: Human Capital Theory (Hct)mentioning
confidence: 99%